'If You Lose Your Youth, You Lose Your Heart and Your Future': Affective Figures of Youth in Community Tensions Surrounding a Proposed Coal Seam Gas Project. Issue 3 (26th January 2018) - Coffey, Julia; Threadgold, Steven; Farrugia, David; Sherval, Meg; Hanley, Jo; Askew, Michael; Askland, Hedda
Abstract: The article discusses the tensions regarding the challenge to balance agriculture with a proposed coal seam gas mine in Narrabri, a regional centre in New South Wales, Australia, which revolved around notions of youth and 'the future'. 'Youth' as a symbolic category were positioned at the heart of the issues associated with land‐use in the region on both sides of the debate. Young people were described throughout the study as an abstract symbol of 'the future'. How exactly 'the future' was related to youth as a symbolic category depended largely on participants' perspectives on the proposed Coal Seam Gas (CSG) mining project. For those who supported the CSG project, the figure of youth signified hope of economic invigoration. For those who opposed the CSG project, the loss of landscape for future generations of youth was a key concern due the potential irreversible environmental impacts associated with the extractive industry in the area. We argue 'youth' becomes a 'figure' imbued with the region's affective anxieties surrounding land‐use change. The concept of affect is developed to aid understanding of the collective and embodied dynamics at play in the differing perspectives on CSG extraction and its impact for the future of Narrabri.